Two-stage genome-wide association designs - Skol, Andrew (Henry Stewart Talks, 2007)
Introduction to genome-wide association studies (GWAs), Construction, analysis and power of two-stage GWAs, Designing optimal two-stage GWAs, Strategies for further reducing the cost of two-stage GWAs, Handling custom arrays when designing optimal GWA